2014
DOI: 10.1016/j.jpor.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic dental biomaterials and CAD/CAM technology: State of the art

Abstract: The clinical uses of these ceramics have met with variable clinical success. Multiple options are now available to the clinicians for the fabrication of aesthetic all ceramic restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
298
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(324 citation statements)
references
References 82 publications
1
298
0
25
Order By: Relevance
“…The CAD/CAM processing procedures commonly used for metal-free restorations are based on the milling of a soft and easily formable, partially crystallised phase. Subsequently the restoration in the established shape is thermally treated to obtain the final mechanical properties and color shade required for oral applications 3,39) . In the PCs, ZLS appears to be brittle, as demonstrated by this study.…”
Section: Discussionmentioning
confidence: 99%
“…The CAD/CAM processing procedures commonly used for metal-free restorations are based on the milling of a soft and easily formable, partially crystallised phase. Subsequently the restoration in the established shape is thermally treated to obtain the final mechanical properties and color shade required for oral applications 3,39) . In the PCs, ZLS appears to be brittle, as demonstrated by this study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of computeraided design/computer-aided machining (CAD/CAM) technology has allowing the manufacture of indirect allceramic restorations using pre-fabricated ceramic blocks, obtained in an industrial and standardized process, which reduces the incorporation of defects, and results in a more homogeneous material [11,12]. CAD/CAM ceramics, such as feldspathic, leucite, lithium disilicate and zirconia, are usually supplied in blocks, with a cuboid geometry, for machining in CAD/CAM systems.…”
Section: O Presente Estudo Avaliou a Influência Da Geometria Do Corpomentioning
confidence: 99%
“…However, no consensus has yet been reached on the clinically acceptable dimension of the interface, ranging the values reported in the literature from 50-200 μm [7][8][9] , and most researchers continue to use the criteria established by McLean and von Fraunhofer 10) . Several studies demonstrated that the final adaptation of the restorations depends on several factors such as finish line, manufacturing technique, porcelain firing and cementing 9,[11][12][13] . Different methods are used to analyze the marginal fit of the restorations, but there is an absence of standardization in the methodology 14) .…”
Section: Introductionmentioning
confidence: 99%